2019
DOI: 10.1111/nyas.14136
|View full text |Cite
|
Sign up to set email alerts
|

The increase in hemoglobin concentration with altitude varies among human populations

Abstract: Decreased oxygen availability at high altitude requires physiological adjustments allowing for adequate tissue oxygenation. One such mechanism is a slow increase in the hemoglobin concentration ([Hb]) resulting in elevated [Hb] in high-altitude residents. Diagnosis of anemia at different altitudes requires reference values for [Hb]. Our aim was to establish such values based on published data of residents living at different altitudes by applying meta-analysis and multiple regressions. Results show that [Hb]is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
70
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 121 publications
9
70
0
3
Order By: Relevance
“…where 15% of men aged 30-39 years and 34% aged 60-69 years present with EE (Monge, Léon-Velarde, & Arregui, 1989). Additionally, a recent meta-analysis demonstrated that there are differences in the haemoglobin concentration between highlander populations (Gassmann et al, 2019) and, in agreement with previous reports (Beall, 2006(Beall, , 2007Beall et al, 2002), that meta-analysis indicated that Andean highlanders have higher haemoglobin concentration and haematocrit compared with other highlander populations (e.g. Sherpa and Ethiopians).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…where 15% of men aged 30-39 years and 34% aged 60-69 years present with EE (Monge, Léon-Velarde, & Arregui, 1989). Additionally, a recent meta-analysis demonstrated that there are differences in the haemoglobin concentration between highlander populations (Gassmann et al, 2019) and, in agreement with previous reports (Beall, 2006(Beall, , 2007Beall et al, 2002), that meta-analysis indicated that Andean highlanders have higher haemoglobin concentration and haematocrit compared with other highlander populations (e.g. Sherpa and Ethiopians).…”
Section: Introductionsupporting
confidence: 86%
“…The Sherpa typically have lower haemoglobin (Hb) concentrations compared with other highlanders at similar altitudes, such as the Peruvian Quechuan (Beall, 2006; Gassmann et al., 2019). Some (Gilbert‐Kawai, Milledge, Grocott, & Martin, 2014; Tremblay, Hoiland, et al., 2018), but not all studies (Liu et al., 2016; Wang et al., 2018), indicate that Sherpa rely on enhanced blood flow and endothelial function to sustain convective oxygen delivery and also on cellular metabolic adaptations to use oxygen more efficiently (Horscroft et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the effect of the altitude on Hb levels is well known. Magnitude of difference found is also impacted by the ethnic group and the sex (Gassmann et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, HIF-2 orchestrates expression of hundreds of hypoxia-induced genes. Even more so, as it has been shown that several ethnicities developed different adaptations when exposed to varying altitudes ( Gassmann et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%